Sharing : culture and the economy in the Internet age - Aigrain, Philippe (Amsterdam : Amsterdam University Press, 2012)
In the past fifteen years, file sharing of digital cultural works between individuals has been at the center of a number of debates on the future of culture itself. To some, sharing constitutes piracy, to be fought against and eradicated. Others see it as unavoidable, and table proposals to compensate for its harmful effects. Meanwhile, little progress has been made towards addressing the real challenges facing culture in a digital world.
Introduction -- [pt. I]. Setting the scene. The Internet and creativity debate -- The value of non-market sharing -- Sustainable resources for creative activities -- [pt. II]. The creative contribution. Which rights for whom? a choice of models -- Defining rights and obligations -- How much? -- Sustainable financing for the commons -- [pt. III]. Implementation. Organization and complementary policy measures -- Usage measurement for equitable rewards -- Clarification and counter-arguments -- From proposal to reality -- Appendixes. Diversity of attention for beginners -- The total cost of rewards and their distribution -- Modeling usage measurement.
Title from publisher's bibliographic system (viewed on 29 Jan 2021).
Keywords: Computer file sharing -- Social aspects; Computer file sharing -- Economic aspects; Creation (Literary, artistic, etc.) -- Social aspects; Creation (Literary, artistic, etc.) -- Economic aspects; Information society; Intellectual property -- Economic aspects; Intellectual property -- Social aspects